Stucco keratosis: a common yet poorly understood phenomenon - Neakiry Kivi; Louise Reiche (New Zealand Medical Student Journal)
1) Retrospective analysis of a database of private clinic patients spanning %3 years. 2) Assessment of all private clinic patients who received a full skin examination for any reason over four weeks. 3) Survey of general practitioners (GPs) and GP registrars in attendance at a local conference.